Toxicity Testing of White Kapul Fruit Rind Extract (Baccaurea macrocarpa) and Component Analysis using Chromatography Method - Kholifatu Rosyidah; Lisda Karmila; Maria Dewi Astuti (Program Studi Kimia, Universitas Lambung Mangkurat, 2022)
White Kapul was used in this study. This study aimed to determine the toxicity of the white Kapul fruit rind extract and its chemical content analysis using TLC and GC-MS. The extraction method used was gradual maceration, namely technical n-hexane, technical ethyl acetate, and technical methanol. Toxicity test using the BSLT method with Artemia salina larvae at the nauplii stage. The test showed that the LC50 value of ethyl acetate extract, methanol extract, and n-hexane extract was 350.87 ppm, 485.61 ppm, and 735.932 ppm, respectively. Based on LC50 values, all extracts had the potential as pesticides. The third extract of white Kapul fruit rind was carried out by TLC analysis to determine the pattern of its compound content. The results of the TLC analysis showed that each extract had different polarity compounds according to the polarity of each solvent. The most active extract, ethyl acetate extract, was further analyzed using GC-MS. There were 32 peak compounds at a retention time of 25.384 to 65.725 minutes in GC-MS analysis. Four compounds with the largest percentage area were gynoluton (58.09%), 15-chloro-4-pentadesene (16.25%), 17- (acetyloxy) -2-methyl-, (2α.,5α ,17β) - estra-3-on (6.07%), and methyl-11-octadesenoate (5.98%). Keywords: Baccaurea macrocarpa, Euphorbiaceae, TLC, toxicity, BSLT, GC-MS